Experimental and numerical investigation of heat confinement during nanoparticle-assisted thermal therapy. (December 2015) - Soni, Sanjeev; Tyagi, Himanshu; Taylor, Robert A.; Kumar, Amod
Abstract: Nanoparticle-assisted thermal ablation therapy has recently evolved as a promising future therapy for cancer treatment. This therapy is advantageous because it is potentially much more selective than traditional methods (surgery or chemotherapy) in terms of destroying cancerous cells while leaving healthy tissue intact. In this study, heat confinement and thus the healthy tissue sparing characteristics, were experimentally investigated. Two Agarose gel samples of cylindrical shape were synthesized for evaluating the heat confinement in the axial and radial directions. A specified region of the gel was embedded with gold nanoparticles which were synthesized in this study (mimicking an injection of nanoparticles to the tumor region), while the rest of the plain gel mimics the surrounding healthy tissue. These Agarose gel samples were irradiated through fiber optic and the spatiotemporal temperature response was measured. A numerical model was also developed and validated against these experiments. The measurements were then extended to real tumor-tissue by taking into account blood perfusion and metabolic heat generation. It is observed that with the proposed approach, heat can be well confined to the nanoparticle embedded region. This study shows that with a well-designed system it is possible to obtain thermal ablation of the tumor region while sparing healthy tissue 3 mm beyond the tumor boundary.